Answer:
34560
Step-by-step explanation:
You have to multiply to get your answer
Hope I'm right...
Hope this helps plz like and brainly :D
Answer:
To find the inverse of:
![f (x)=\dfrac{4}{x-2}-1](https://tex.z-dn.net/?f=f%20%28x%29%3D%5Cdfrac%7B4%7D%7Bx-2%7D-1)
Set the function to y:
![\implies y=\dfrac{4}{x-2}-1](https://tex.z-dn.net/?f=%5Cimplies%20y%3D%5Cdfrac%7B4%7D%7Bx-2%7D-1)
Rearrange to make x the subject:
![\implies y+1=\dfrac{4}{x-2}](https://tex.z-dn.net/?f=%5Cimplies%20y%2B1%3D%5Cdfrac%7B4%7D%7Bx-2%7D)
![\implies (y+1)(x-2)=4](https://tex.z-dn.net/?f=%5Cimplies%20%28y%2B1%29%28x-2%29%3D4)
![\implies xy-2y+x-2=4](https://tex.z-dn.net/?f=%5Cimplies%20xy-2y%2Bx-2%3D4)
![\implies xy+x=2y+6](https://tex.z-dn.net/?f=%5Cimplies%20xy%2Bx%3D2y%2B6)
![\implies x(y+1)=2y+6](https://tex.z-dn.net/?f=%5Cimplies%20x%28y%2B1%29%3D2y%2B6)
![\implies x=\dfrac{2y+6}{y+1}](https://tex.z-dn.net/?f=%5Cimplies%20x%3D%5Cdfrac%7B2y%2B6%7D%7By%2B1%7D)
Swap x and y:
![\implies y=\dfrac{2x+6}{x+1}](https://tex.z-dn.net/?f=%5Cimplies%20y%3D%5Cdfrac%7B2x%2B6%7D%7Bx%2B1%7D)
Change y to the inverse of the function sign:
![\implies f](https://tex.z-dn.net/?f=%5Cimplies%20f)
![\:^{-1}(x)=\dfrac{2x+6}{x+1}](https://tex.z-dn.net/?f=%5C%3A%5E%7B-1%7D%28x%29%3D%5Cdfrac%7B2x%2B6%7D%7Bx%2B1%7D)
Rewrite g(x) as a fraction:
![g(x)=\dfrac{3}{x+2}-2](https://tex.z-dn.net/?f=g%28x%29%3D%5Cdfrac%7B3%7D%7Bx%2B2%7D-2)
![\implies g(x)=\dfrac{3}{x+2}-\dfrac{2(x+2)}{x+2}](https://tex.z-dn.net/?f=%5Cimplies%20g%28x%29%3D%5Cdfrac%7B3%7D%7Bx%2B2%7D-%5Cdfrac%7B2%28x%2B2%29%7D%7Bx%2B2%7D)
![\implies g(x)=\dfrac{3-2(x+2)}{x+2}](https://tex.z-dn.net/?f=%5Cimplies%20g%28x%29%3D%5Cdfrac%7B3-2%28x%2B2%29%7D%7Bx%2B2%7D)
![\implies g(x)=\dfrac{3-2x-4}{x+2}](https://tex.z-dn.net/?f=%5Cimplies%20g%28x%29%3D%5Cdfrac%7B3-2x-4%7D%7Bx%2B2%7D)
![\implies g(x)=-\dfrac{2x+1}{x+2}](https://tex.z-dn.net/?f=%5Cimplies%20g%28x%29%3D-%5Cdfrac%7B2x%2B1%7D%7Bx%2B2%7D)
Therefore, as the inverse of f(x) ≠ g(x), the functions are NOT inverses of each other
Answer:
the y-intercept is 8 and the slope is -4/3 .
Step-by-step explanation:
This question is incomplete.
The complete question says;
The two-way table shows the number of hours students studied and whether they studied independently or with a study group.
What is the relative frequency of students that studied independently for more than 2 hours to the total number of students that studied independently?
a) 0.4 c) 0.25
b) 0.33 d) 0.11
Table is attached as image
Answer: C (0.25)
The number of students that studied for more than 2 hours as given in the table are 4.
The total number of people that studied independently include those that studied less than 2 hours and those that studied for more than 2 hours.
Those that studied less than 2 hours independently are 12.
Those that studied more than 2 hours independently are 4.
Hence the total number of people that studied independently is 16.
Therefore the relative frequency of students that studied independently for more than 2 hours to the total number of students that studied independently would be = 4/16 = 1/4 = 0.25.